Reformulasi Model Pembelajaran Kitab Kuning di Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan - Thoha, Mohammad (TADRIS: Jurnal Pendidikan Islam, 2021)
This article reveals the efforts made by Maktab Nubdzatul Bayan at Islamic boarding school Mambaul Ulum Bata-Bata Pamekasan in providing a new breakthrough in accelerating the mastery of the arabic book for children of basic education age. The pattern of accelerated learning as the key to this movement has proven to lead to mastery of the arabic book which is relatively short for the age of the children. With a qualitative approach and photographing objects naturally, this research data was obtained through interviews, activity observations and document review. The results of the study show that the arabic book learning reformulation is carried out by: a button-up pattern of policy-making; placement of students as a learning center (student centered); implementation of student-based supervision; mentoring attached to junior students; spiritual strengthening of caregivers; and small group based learning; competency test of prospective graduates, and appreciation of student achievement. The success of this effort is influenced by several factors: the common determination of all parties; the ratio of comparison between supervisors and students is ideal; standard study and dormitory facilities; conducive learning environment and great caregiver support.